The Effect Of Different Feed Combinations On The Growth Rate, Efficiency And Survival Rate Of Juvenile Catfish (Clarias Sp.) - Vera Ardelia; Ria Fahleny; Susi Damayanti (Fakultas Pertanian Universitas Muara Bungo, 2023)
Catfish is classified as an omnivorous fish and has fast growth, has the ability to tolerate wide-ranging environmental parameters. The study aims to determine the length growth, weight growth, survival rate, feed efficiency and to determine the water duality in the Catfish (Clarias sp.) juvenile pond with differend feed treatments. The results of research showed that different feeding had an effect on the growth of catfish (Clarias sp.) juveniles. Length growth ranged from 9.78-10.8 cm, the highest value was in treatment 3, namely 10.8 cm and the lowest was in treatment 1, namely 9.78 cm. Weight growth ranged from 24-39 g, the highest value was in treatment 3, namely 39g and the lowest was in treatment 1, namely 24g. The survival rate ranged from 0.95-1%, the highest value was in treatment 3, namely 1% and the lowest was in treatment 1, namely 0.95%. feed efficiency ranged from 2.124-3.55%, the hinghest value was found in treatment 3, namely 3.55% and the lowest in treatment 1, namely 2.124%. the water quality during the research was still in the appropriate range for growth and survival of catfish (Clarias sp.) juveniles.